Maqasid al-Sharia and Forced Displacement: An Islamic Ethical Analysis of Women’s and Children’s Protection in Borno State - Jajere , Zara Muhammad (Goodwood Publishing, 2026)
Purpose: This study examines the conditions and vulnerabilities of women and children internally displaced by the Boko Haram insurgency in Borno State, Nigeria, through the analytical lens of maqasid al-sharia (the higher objectives of Islamic law). It seeks to explore how Islamic ethical frameworks can inform protection responses in Muslim-majority humanitarian contexts. Research Methodology: The study employs a PRISMA-ScR guided scoping review of academic literature, humanitarian reports, and policy documents published between 2010 and 2025. The review systematically synthesizes evidence related to displacement-induced risks affecting women and children. Results: The findings indicate that internally displaced women and children face persistent threats, including gender-based violence, food insecurity, disrupted education, psychosocial trauma, and economic marginalization. These conditions reflect systematic violations of the core maqasid, particularly the preservation of life, dignity, intellect, lineage, and property. Conclusions: A maq??id-based framework provides a coherent ethical foundation for aligning Islamic values with contemporary humanitarian protection norms, while offering a normative critique of harmful practices within displacement settings. Limitations: The study relies on secondary data sources and does not include primary field research, which may limit contextual specificity. Contribution: The article contributes to interdisciplinary debates on faith-sensitive humanitarianism by integrating Islamic legal theory into rights-based protection discourse in conflict-induced displacement contexts.